2019
DOI: 10.1093/mnras/stz971
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a pulsar-powered bow shock nebula in the Small Magellanic Cloud supernova remnant DEM S5

Abstract: We report the discovery of a new Small Magellanic Cloud Pulsar Wind Nebula (PWN) at the edge of the Supernova Remnant (SNR) DEM S5. The pulsar powered object has a cometary morphology similar to the Galactic PWN analogs PSR B1951+32 and 'the mouse'. It is travelling supersonically through the interstellar medium. We estimate the Pulsar kick velocity to be in the range of 700-2000 km s −1 for an age between 28-10 kyr. The radio spectral index for this SNR-PWN-pulsar system is flat (-0.29 ± 0.01) consistent with… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 84 publications
1
13
0
Order By: Relevance
“…B.1), first studied with ROSAT and XMM-Newton in Haberl et al (2000) and Filipović et al (2008), respectively. The presence of an X-ray point-like source within the remnant associated to resolved radio emission recently led Alsaberi et al (2019) to the discovery of a candidate pulsar wind nebula (PWN). The Xray analysis of the diffuse emission (SNR component) in this work, which was also presented in Alsaberi et al (2019), reveals that the emission arises from shocked ambient medium, as no abundance enhancement is found.…”
Section: Notes On Individual Smc Snrsmentioning
confidence: 99%
“…B.1), first studied with ROSAT and XMM-Newton in Haberl et al (2000) and Filipović et al (2008), respectively. The presence of an X-ray point-like source within the remnant associated to resolved radio emission recently led Alsaberi et al (2019) to the discovery of a candidate pulsar wind nebula (PWN). The Xray analysis of the diffuse emission (SNR component) in this work, which was also presented in Alsaberi et al (2019), reveals that the emission arises from shocked ambient medium, as no abundance enhancement is found.…”
Section: Notes On Individual Smc Snrsmentioning
confidence: 99%
“…Recent CO observations using the Atacama Submillimeter Telescope Experiment (ASTE), Mopra, and Atacama Large Millimeter/submillimeter Array (ALMA) revealed clumpy molecular clouds associated with the X-ray bright LMC SNRs with an angular resolution of 2 ′′ -45 ′′ , corresponding to the spatial resolution of 0.5-11 pc (Sano et al 2015(Sano et al , 2017b(Sano et al ,c, 2018(Sano et al , 2019aYamane et al 2018). Most recently, Alsaberi et al (2019) found an Hi cavity interacting with the SMC SNR DEM S5. The Hi data was obtained using the Australian Square Kilometer Array Pathfinder (ASKAP) with an angular resolution of ∼30 ′′ , corresponding to the spatial resolution of ∼9 pc at the SMC distance.…”
Section: Introductionmentioning
confidence: 99%
“…Observations with XMM-Newton have also allowed us to resolve and identify new pulsar wind nebulae (PWNe) and X-ray binaries in SNRs in the MC. 2-4.5 keV) images of the SMC SNR DEM S5 with contours of the 1320 MHz radio continuum (Alsaberi et al 2019). In X-rays there is a soft shell emission and a harder point source which coincides with the head of the bow-shock PWN seen in radio.…”
Section: Composite Supernova Remnantsmentioning
confidence: 86%
“…There are three known composite SNRs with a thermal shell and a PWN observed in X-rays in the LMC (SNR N206, J0540-6919 [N158A], and J0453-6829) and one in the SMC (SNR IKT 16). In addition, we have discovered a pulsar-powered bow-shock nebula in the SMC SNR DEM S5 (Alsaberi et al 2019). This SNR is bright in the optical spectrum and show filamentary structures in the shell (Figure 3, left).…”
Section: Composite Supernova Remnantsmentioning
confidence: 95%